1965
DOI: 10.1111/j.1365-3091.1965.tb01550.x
|View full text |Cite
|
Sign up to set email alerts
|

THE USE OF ANISOTROPY OF MAGNETIC SUSCEPTIBILITY IN THE ESTIMATION OF SEDIMENTARY FABRIC1

Abstract: The feasibility is discussed of using anisotropy of magnetic susceptibility to find preferred directions of grain orientation and current directions in sediments, and it is concluded that it should be possible to find these directions in silts and sands containing between 0.01 and 1 % of magnetite.Some examples are given of the use of the method under controlled conditions, and it is shown to give the same result as optical grain orientation determination in one example and to predict the same current directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(77 citation statements)
references
References 4 publications
2
74
0
1
Order By: Relevance
“…Shape and orientation of the anisotropy ellipsoid was used to detect whether disturbances were from the coring process or from natural origin (e.g. Rees (1965); Demory et al, this issue).…”
Section: Methodsmentioning
confidence: 99%
“…Shape and orientation of the anisotropy ellipsoid was used to detect whether disturbances were from the coring process or from natural origin (e.g. Rees (1965); Demory et al, this issue).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of depositional AMS in sediments have shown that the shape and orientation of the magnetic fabric can be related to different sedimentological processes during the deposition of particles from suspension in water (Ellwood, 1980;Rees, 1965;Rees et al, 1968;Rees & Woodall, 1975;Weiler, 2007). The initial sedimentary fabrics are generally determined by gravity and currents.…”
Section: Magnetic Fabric Resultsmentioning
confidence: 99%
“…The credibility of the AMS fabric as a paleocurrent and depositional indicator is known from work on natural (Ellwood and Ledbetter, 1979;Abdeldayem et al, 1999;Liu et al, 2001) and laboratory deposited sediments (Rees, 1965;Rees and Woodall, 1975). Furthermore, AMS has been used to evaluate flow vectors in lava flows (Cañón-Tapia et al, 1996Cañón-Tapia and Walker, 1998;MacDonald et al, 1992) and pyroclastic deposits (e.g., Ellwood, 1982;Incoronato et al, 1983;Knight et al, 1986;Wolff et al, 1989;MacDonald and Palmer, 1990;Hillhouse and Wells, 1991;Seaman et al, 1991;Ort, 1993;Cagnoli and Tarling, 1997;MacDonald et al, 1998;Ort et al, 1999), in order to determine vent locations, or transport and depositional processes at different distances from the vent (e.g., Fisher et al, 1993;Baer et al, 1997;Le Pennec et al, 1998;Palmer and MacDonald, 1999).…”
mentioning
confidence: 99%
“…The initial fabrics are largely determined by gravitational and hydrodynamic forces and, hence, are mainly controlled by the size, shape and mass of detrital grains and velocity of the medium in which they are being transported (Tarling and Hrouda, 1993). In these sediments, the current would usually be parallel to the K 1 axis; in favorable conditions its absolute direction may be inferred from the tilting direction of the K 3 axis (Rees, 1965;Tarling and Hrouda, 1993;Tarling and Shi, 1995;Piper et al, 1996;Abdelayem et al, 1999). However, the current could be perpendicular to K 1 if the flow is strong enough and the grains are fine (Ellwood and Ledbetter, 1977).…”
mentioning
confidence: 99%